A large-scale shift of cropland structure profoundly affects grain production in the cold region of China. (20th July 2021) - Pan, Tao; Zhang, Chi; Kuang, Wenhui; Luo, Geping; Du, Guoming; DeMaeyer, Philippe; Yin, Zherui
Abstract: Rapid cropland reformation is occurring in the cold region of China (hereafter referred to as Cold China), affecting national crop structure production. In addition, different agricultural systems, including state and private farms, exist in Cold China. To date, the different effects of cropland reformation on grain production in state and private farms are lacking. Focusing on this issue and using synergistic methodology, results revealed that the transformation from upland crops to paddy field was principal land change across Cold China from 1990 to 2015. This transformation increased grain production by 434.0 × 10 4 t, accounting for over 14.0% of the total grain production increase in Cold China (i.e., from 748.0 × 10 4 t in 1990–3785.1 × 10 4 t in 2015) in the study period, showing positive feedback on grain security. Between two agricultural systems, more intensive transformation area (10993.3 km 2 vs. 4673.5 km 2 ) and a larger contribution to grain production increase (11.1% vs. 3.2%) occurred on state compared with private farms. Crop structure also evolved differently in the two agricultural systems. Dominant crop changed from soybean (1990–2000) to rice paddy (2000–2015) on state farms but from soybean (1990–2005) to corn (2005–2015) on private farms, indicating state farms focused on human dietary supply and private farms mainly served industrial needs. This study showed cropland reformation in response to global food trade increased grain production in Cold China. State farms were more efficient in such reformation; more market-oriented policies should be designed to encourage the reformation on private farms. This study provided a new reference for other regions/countries' investigation on cropland and food structural security in different agricultural systems. Graphical abstract: Image 1 Highlights: The shift from upland crops to paddy field was principal land change in Cold China. Positive effect on food sustainability was observed from upland crops to paddy field. Different roles of state and private farms in grain production were revealed.